SENI TARI DAN DRAMA DALAM KONTEKS PENDIDIKAN DAN BUDAYA KONTEMPORER - Loustiawaty, Lousy; Sofia Zein, Nadia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Dance and drama are integral parts of the performing arts that play a vital role in contemporary education and culture. They serve not only as a means of aesthetic expression and preservation of cultural values, but also as effective pedagogical media in developing students' cognitive, affective, and psychomotor abilities. In the context of modern education, dance and drama are able to provide active, creative, and meaningful learning, while simultaneously responding to the challenges of globalization, technological development, and socio-cultural change. Through movement exploration, staging, and role-playing activities, students are trained to develop creativity, communication skills, collaboration, empathy, and cultural awareness. This study uses a qualitative descriptive approach with a literature review method of various relevant scientific sources, such as journal articles, books, and research results from the last five years that discuss dance and drama in the context of contemporary education and culture. The results of the study indicate that the integration of dance and drama in learning makes a significant contribution to holistic education, as it is able to simultaneously connect the intellectual, emotional, social, and physical aspects of students. In addition, the use of performing arts in education also plays a role in strengthening cultural identity, fostering tolerance, and increasing appreciation for diversity. Thus, dance and drama can offer a relevant and contextual learning approach in forming a generation that is creative, has character, and is adaptive to the dynamics of contemporary culture.